2001
DOI: 10.2355/isijinternational.41.1350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermomechanical Processing on the Hot Ductility of a Nb-Ti Microalloyed Steel.

Abstract: Many attempts have been made to understand the problem of transverse cracking in continuous casting process. Much of this research has involved the study of hot ductility using 'conventional' isothermal hot ductility testing. In these tests, the specimens were isothermally tensile tested to fracture, at temperatures achieved by cooling from a solutionizing temperature, close to the solidus, or above the liquidus. These studies showed that hot ductility at the test temperature is highly depended on the thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Currently S. Yue et al conducted hot ductility study of the Nb-Ti steel by using similar experimental procedures to the present case, where it was reported that g grain size obtained after melting and solidification was around 120 mm, although it was not referred about it's coincidence to actually observed g grain size in the solidified steel billet. 23) G. E Ruddle et al studied direct rolling of thin slabs of the Ti-Nb steel by Gleeble simulation of continuous casting, and reported that g grain size after solidification was varied from 525 to 148 mm as the cooling rate increased from 0.5 to 15 K/s. 6) Comparing with these results, g grain size obtained by the present melting and solidification experiment was much larger and corresponded more closely to g grain size actually observed in the solidified strand cast slab with thickness over 200 mm.…”
mentioning
confidence: 99%
“…Currently S. Yue et al conducted hot ductility study of the Nb-Ti steel by using similar experimental procedures to the present case, where it was reported that g grain size obtained after melting and solidification was around 120 mm, although it was not referred about it's coincidence to actually observed g grain size in the solidified steel billet. 23) G. E Ruddle et al studied direct rolling of thin slabs of the Ti-Nb steel by Gleeble simulation of continuous casting, and reported that g grain size after solidification was varied from 525 to 148 mm as the cooling rate increased from 0.5 to 15 K/s. 6) Comparing with these results, g grain size obtained by the present melting and solidification experiment was much larger and corresponded more closely to g grain size actually observed in the solidified strand cast slab with thickness over 200 mm.…”
mentioning
confidence: 99%
“…It normally increases the tensile properties and toughness (Dhua, 2003) without reducing ductility or brittle fracture resistance (Akhlaghi, 2001;Jahazi & Egbali, 2000). With controlled rolling it is possible to refine the ferrite structures directly after finish rolling or by using additional accelerated cooling.…”
Section: Issues and Objectivementioning
confidence: 99%
“…As a result, casting and hot rolling have to be performed within a very narrow process window in order to avoid cracking. This is described in the literature on these steels in papers dealing with direct strip casting 9, high temperature strength and crack susceptibility 10, thermomechanical rolling 11, and the effect of the reduction ratio during the first pass in hot rolling 8.…”
Section: State Of the Art And Objectivesmentioning
confidence: 99%